SIMULTANEOUS ESTIMATION OF LAMIVUDINE, ABACAVIR AND DOLUTEGRAVIR BY UPLC METHOD - Dubey, Somshankar; Duggirala, Mahesh (International Journal of Applied Pharmaceutics, 2018)
Objective: To develop a simple, rapid, sensitive and effective reverse phase ultra-performance liquid chromatographic method (RP-UPLC) for simultaneous quantification of lamivudine, abacavir and dolutegravir in pure and tablet dosage forms. Methods: Chromatographic separation was performed by using Waters-ACQUITY UPLC system equipped with auto sampler, photodiode array (PDA) detector, zodiac sil RP C18 (4.6 mm × 250 mm, 3.0 µm) column, phosphate buffer (pH 3.0) and methanol in the ratio of 30:70 %v/v have been delivered at a flow rate of 0.25 ml/min and the detection was carried out using a Ultraviolet (UV) detector at a wavelength of 260 nm at ambient column temperature. The mobile phase was used as diluent. Results: The retention time (Rt) for lamivudine, abacavir and dolutegravir were 1.763, 2.247 and 3.175 min respectively. A good linear response was obtained in the range of 15-75 µg/ml, 30-150 µg/ml and 2.5-12.5 µg/ml, respectively. The Limit of Detection (LOD) values were found to be 0.021, 0.330 and 0.038 µg/ml, respectively and the Limit of Quantitation (LOQ) values were 0.056, 1.320 and 0.095 µg/ml, respectively. Conclusion: It was concluded that the developed RP-UPLC method was effective, suitable and conducive for analyzing lamivudine, abacavir and dolutegravir in pharmaceutical formulations. The method was quantitatively evaluated in terms of precision, linearity, accuracy (recovery), selectivity and robustness in accordance with standard guidelines.